Postauricular Incision Versus Conventional Transcervical Incision in Second Branchial Cleft Cyst Excision: A Systematic Review and Meta-Analysis. Issue 8 (26th November 2022) - Ho, Che-Fang; Yang, Tsung-Han; Hsin, Li-Jen; Yang, Shih-Wei; Tsai, Yao-Te; Tsai, Ming-Shao; Yang, Cheng-Ta; Lee, Yi-Chan
Abstract : Surgical removal is the treatment of choice for second branchial cleft cysts (SBCCs), which are congenital anomalies. The conventional procedure is performed through a transcervical approach, which would lead to a visible scar in the anterior neck. Conversely, the postauricular approach could keep the scar in the hairline or retroauricular sulcus, rendering it almost invisible after the surgery. The purpose of this meta-analysis was to evaluate the differences between the postauricular and conventional transcervical approaches to SBCC excision. A systematic review was performed using PubMed, Embase, and the Cochrane Library to identify studies comparing outcomes of SBCC surgery via postauricular and conventional transcervical approaches. The data of interest were analyzed with Comprehensive Meta-Analysis software (version 3). The data of interest were analyzed by calculating the risk difference (RD), the standardized mean difference, and the mean difference (MD) with the 95% confidence interval (CI). Three studies were eligible for the final analysis. The pooled analysis demonstrated that the cosmetic satisfaction score was significantly higher with the postauricular approach (standardized mean difference, 2.12; 95% CI, 0.68–3.56). The operative duration was significantly longer with the postauricular approach than with the conventional transcervical approach (MD, 12.81; 95% CI, 2.39–23.23). The incidences of postoperative marginal mandibular nerve palsy (RD, 0.00; 95% CI, −0.09 to 0.09), bleeding complications (RD, −0.02; 95% CI, −0.09 to 0.05), salivary complications (RD, −0.00; 95% CI, −0.07 to 0.06), cyst size (MD, 0.02; 95% CI, −0.96–0.99), and length of hospital stay (MD, −2.50; CI, −7.30 to 2.30) were comparable between the 2 groups. The postauricular approach is feasible for use in SBCC excision and yields better cosmetic outcomes, a longer operative duration, and a similar rate of complications.